Peningkatan Literasi Pelindungan Data Pribadi Bagi Kelompok Rentan Di Kampung Inspirasi Melalui Pendekatan Hukum Klinis - Maruf, Irma Rachmawati; Rifqi Noval, Sayid Muhamad; Sumantry, Deden; Md. Noor, Zakhiri; Eka Yudistira, Dika (Syntax Corporation, 2025)
Personal Data Protection Outreach for Vulnerable Groups in Kampung Inspirasi through a Clinical Legal Approach The rapid advancement of digital technology has significantly increased the risk of personal data misuse, particularly among vulnerable groups such as housewives, children, and the elderly. Limited legal and digital literacy in Desa Cijambe, Bandung Regency, underscores the urgent need for public legal education on personal data protection, especially in the context of Indonesia’s Law Number 27 of 2022 on Personal Data Protection (PDP Law). This community service program aimed to enhance public awareness and understanding of the importance of safeguarding personal data during everyday digital interactions. The program employed a Clinical Legal Education (CLE) approach through student-based learning, interactive workshops, roleplay simulations, and live legal clinics. Evaluation results showed a significant improvement in participants’ comprehension, with average scores increasing from 67.5 (pre-test) to 81.5 (post-test), and learning completion rising from 72.5% to 92.5%. Participants demonstrated active engagement and enthusiasm during discussions and practical sessions. These findings indicate that the CLE method is effective in delivering legal material in a practical and accessible manner. The program not only strengthened participants’ legal literacy but also laid a foundation for the replication of similar outreach activities in other communities.